Molecular Modelling of Selected Phthalates and Their Interactions with Stationary Phases in Solid-Phase Microextraction - Dariusz Wideł; Jerzy Oszczudłowski; Zygfryd Witkiewicz (Adsorption Science & Technology)
In this work, solid-phase microextraction of six phthalates from methanol and aqueous solutions were carried out. Polar polyacrylate (PA) and non-polar polydimethylsiloxane (PDMS) were used as stationary phases. HyperChem 8.0 software was used for the optimization of the geometry of these six phthalates and their interactions with stationary phases. Extracted samples were analyzed using gas chromatography coupled with mass spectrometry. In the analysis of phthalates extracted from methanol solution, the best extraction efficiency was obtained for the PA phase, whereas for the extraction from aqueous solution, higher efficiency was obtained for the PDMS phase.